Exploring the Physiological Effects of Jogging During Ramadan Fasting: Impact on Physiology and Performance in University Students - Valentino, Bayu; Yacob, Mohamad Rozi Bin; Muhammad; Pranoto, Adi; Andriana, Laily Mita (Universitas Negeri Surabaya, 2025)
Purpose: Low physical activity in adolescents causes the prevalence of obese adolescents in Indonesia to increase from year to year; in 2018, 20% of adolescents were found to be obese. The obesity factor provides or indicates the occurrence of non-communicable diseases. This study aimed to identify the effects of a combination of Ramadhan fasting and 30 minutes of jogging exercise on body composition profile and fitness. Materials and Methods: Ten adolescents aged 18-19 years participated in this study. They fasted during Ramadan and performed physical exercise 4 times a week for 3 weeks. Body composition measurements using BC 545N Tanita segmental body composition monitor (body weight, body mass index, water percentage, visceral fat), blood glucose level measured with EasyTouch GCU, and the 20-metre multistage fitness test (20 MFT) measures aerobic fitness by predicting maximum oxygen uptake (VO2Max), Speed (20-Meter Sprint Test) and Power (counter movement jump). A descriptive test and a paired sample t-test were used to evaluate the results of this study. Result: The results of this study, there were significant differences (p < 0.05) between before and after training and Ramadhan fasting in 3 times a week for 4 weeks in body weight reduced by 4.33%, BMI reduced by 2.90%, water percentage increased by 3.14%, visceral fat reduced by 17.35%, blood glucose levels slight increase by 8.20%, and VO2Max increased 11.77%. Conclusion: This study concludes that combining Ramadan fasting with 30-minute jogging affects body composition, glucose levels, and fitness. The health profile during adolescence is important to consider because it will impact health later in life.